Chronic kidney disease in congenital heart disease patients: a narrative review of evidence - Morgan, Catherine (Can J Kidney Health Dis, 2015)
PURPOSE OF REVIEW: Patients with congenital heart disease have a number of risk factors for the development of chronic kidney disease (CKD). It is well known that CKD has a large negative impact on health outcomes. It is important therefore to consider that patients with congenital heart disease represent a population in whom long-term primary and secondary prevention strategies to reduce CKD occurrence and progression could be instituted and significantly change outcomes. There are currently no clear guidelines for clinicians in terms of renal assessment in the long-term follow up of patients with congenital heart disease. Consolidation of knowledge is critical for generating such guidelines, and hence is the purpose of this view. This review will summarize current knowledge related to CKD in patients with congenital heart disease, to highlight important work that has been done to date and set the stage for further investigation, development of prevention strategies, and re-evaluation of appropriate renal follow-up in patients with congenital heart disease. SOURCES OF INFORMATION: The literature search was conducted using PubMed and Google Scholar. FINDINGS: Current epidemiological evidence suggests that CKD occurs in patients with congenital heart disease at a higher frequency than the general population and is detectable early in follow-up (i.e. during childhood). Best evidence suggests that approximately 30 to 50 % of adult patients with congenital heart disease have significantly impaired renal function. The risk of CKD is higher with cyanotic congenital heart disease but it is also present with non-cyanotic congenital heart disease. Although significant knowledge gaps exist, the sum of the data suggests that patients with congenital heart disease should be followed from an early age for the development of CKD. IMPLICATIONS: There is an opportunity to mitigate CKD progression and negative renal outcomes by instituting interventions such as stringent blood pressure control and reduction of proteinuria. There is a need to invest time, thought and money to fill existing knowledge gaps to improve health outcomes in this population. This review should serve as an impetus for generation of follow-up guidelines of kidney health evaluation in patients with congenital heart disease.